2019
DOI: 10.1186/s12958-019-0526-3
|View full text |Cite
|
Sign up to set email alerts
|

Hashimoto’s thyroiditis impairs embryo implantation by compromising endometrial morphology and receptivity markers in euthyroid mice

Abstract: BackgroundAlthough thyroid dysfunction caused by Hashimoto’s thyroiditis (HT) is believed to be related to implantation failure due to the underdevelopment of the receptive uterus, it is unknown whether HT itself, even in the euthyroid state, impairs embryo implantation associated with endometrial receptivity defects. To address whether HT itself can affect endometrial receptivity accompanied by implantation alterations, a euthyroid HT model was established in mice.MethodsFemale NOD mice were immunized twice w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 78 publications
0
7
0
Order By: Relevance
“…The study of Merhan Dorostghoal 65 demonstrate that the endometrial ER‐α expression may lead to defects in uterine receptivity and contribute to unexplained infertility. Furthermore, Zhangbi Wu 66 indicated that TPO‐Ab induces a non‐receptive endometrial milieu in the euthyroid state, which may underlie the detrimental effects of Hashimoto's thyroiditis (HT) itself on embryo implantation. More research is needed to identify the role of thyroid autoantibodies on implantation.…”
Section: Discussionmentioning
confidence: 99%
“…The study of Merhan Dorostghoal 65 demonstrate that the endometrial ER‐α expression may lead to defects in uterine receptivity and contribute to unexplained infertility. Furthermore, Zhangbi Wu 66 indicated that TPO‐Ab induces a non‐receptive endometrial milieu in the euthyroid state, which may underlie the detrimental effects of Hashimoto's thyroiditis (HT) itself on embryo implantation. More research is needed to identify the role of thyroid autoantibodies on implantation.…”
Section: Discussionmentioning
confidence: 99%
“…The association between TAI and miscarriage remains a matter of debate: it has been suggested that women with TAI have a more generalized autoimmune activity [ 5 , 6 ], leading to an increased fetal loss. Recent data suggest that euthyroid women are affected by TAI-impaired embryo implantation through induction of endometrial receptivity defects [ 7 ]. However, few studies have demonstrated the efficacy of therapies which modulate the immune function in preventing miscarriage [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of thyroid dysfunction, the absolute number and percentage of T-cells, T-helper (Th) cells, B-cells and natural killer (NK) cells were not different between women with and without TAI (32,33). Since no difference in serum oestradiol or progesterone levels were observed between groups, these findings could indicate that TAI induces a non-receptive endometrial milieu that may underlie the detrimental effects on embryo implantation (34). However, in most clinical studies similar implantation rates were noted between women with -and without TAI, although with more first-trimester miscarriages in women with TAI (15,35).…”
Section: Infertility In Euthyroid Women With Thyroid Autoimmunitymentioning
confidence: 89%